Symbiosis, dysbiosis and the impact of horizontal exchange on bacterial microbiomes in higher fungus-gardening ants - Blake Bringhurst; Matthew Greenwold; Katrin Kellner; Jon N. Seal (Scientific Reports, 2024)
Abstract Advances in our understanding of symbiotic stability have demonstrated that microorganisms are key to understanding the homeostasis of obligate symbioses. Fungus-gardening ants are excellent model systems for exploring how microorganisms may be involved in symbiotic homeostasis as the host and symbionts are macroscopic and can be easily experimentally manipulated. Their coevolutionary history has been well-studied; examinations of which have depicted broad clade-to-clade specificity between the ants and fungus. Few studies hitherto have addressed the roles of microbiomes in stabilizing these associations. Here, we quantified changes in microbiome structure as a result of experimentally induced horizontal exchange of symbionts. This was done by performing cross-fostering experiments forcing ants to grow novel fungi and comparing known temporally unstable (undergoing dysbiosis) and stable combinations. We found that fungus-gardening ants alter their unstable, novel garden microbiomes into configurations like those found in native gardens. Patterns of dysbiosis/symbiosis appear to be predictable in that two related species with similar specificity patterns also show similar patterns of microbial change, whereas a species with more relaxed specificity does not show such microbiome change or restructuring when growing different fungi. It appears that clade-to-clade specificity patterns are the outcomes of community-level interactions that promote stability or cause symbiotic collapse.